The impact of using KICK Training to learn basic football skills for middle school students - Mohammed Jasim, Alaa; Amer Saadoun, Dalya; Fadhil Waal, Wisam (International Journal of Psychosocial Rehabilitation, 2020)
Football is one of the most popular games in the world, which has witnessed an evolution in learning and training methods for young age groups. The research problem is limited by the lack of use of assistive devices and the lack of this device/tool in schools in teaching football for beginners. The researchers assumed the training tool (KICK Training) has a positive impact in learning basic football skills. For the research sample, the experimental method was used to suit the research problem. The researchers chose the middle school Moaz bin Jabal and by lot class (D) was chosen for the research. The whole class of 16 students was randomly divided into two groups, (8) students represent the experimental group and (8) students represent the control group. The researchers got to the following conclusions that the use of the helping tool (KICK Training) has proven to be more effective in learning basic football skills like passing, controlling and receiving the ball.